Electron and X-Ray Methods of Ultrafast Structural Dynamics: Advances and Applications - Chergui, Majed; Zewail, Ahmed H. (Chemphyschem, 2009)
In this contribution, we highlight the state of the art in the determination of structures with ultrafast electrons and X‐rays. We provide our perspectives and reflections on the principles, techniques and methods, and on applications from different disciplines, with some focus on physical, chemical and biological structures. Although this article is not a survey of all the work done with these techniques, it provides a comprehensive referencing to current research. State of the art techniques: Ultrafast electron microscopy and X‐ray diffraction methods (see figure) unravel structural dynamics with atomic‐scale resolution in systems ranging from small molecules to crystals and from materials to biological assemblies. The applications span structures in the gas phase and at interfaces as well as in the condensed phase.